Recent Progress on Circular RNA Research in Acute Myeloid Leukemia - Jamal, Muhammad; Song, Tianbao; Chen, Bei; Faisal, Muhammad; Hong, Zixi; Xie, Tian; Wu, Yingjie; Pan, Shan; Yin, Qian; Shao, Liang; Zhang, Qiuping (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is a myeloid malignancy characterized by the proliferation of abnormal and immature myeloid blast in bone marrow. Circular RNA (circRNA) is a novel class of long non-coding RNA with a stable circular conformation regulating various biological processes. The aberrant expression of circRNA and its impact on AML progression has been reported by a number of studies. Despite recent advances in circRNA research, understanding the leukemogenic mechanism of circRNA remains suboptimal. Therefore, translating the current circRNA related research into clinical practices is challenging. This review provides information about functional role and research progress of circRNAs in AML with emphasis on mechanistic insights. The current challenges and opportunities associated with the circRNA related therapeutic research in AML are also outlined.